Desain dan Implementasi Pengolahan Citra Pada Sistem Autonomous Sentry Gun Menggunakan CMUCam5 dan Arduino Mega 2560 - Eki Ahmad Zaki Hamidi; Firman Febrianto Asmoro; Mufid Ridlo Effendi (Infotekmesin, 2024)
Security is a top priority in various sectors, including military, industrial, and household security. Conventional security systems often require continuous human surveillance, reducing effectiveness and responsiveness. This research aims to address these issues by designing and implementing an Autonomous Sentry Gun system using the CMUCam5 module and Arduino Mega 2560 microcontroller. The system detects and tracks targets automatically, utilizing CMUCam5's vision tracking capabilities to identify objects based on color and shape. The Arduino Mega 2560 serves as the main processing unit, controlling motor movements and firing mechanisms based on data from the camera module. Test results show that the system can detect and follow targets with high accuracy under various lighting conditions. The color yellow with RGB code 255, 255, 0 has the longest tracking distance of 450 cm, while the color purple with RGB code 128, 0, 128 has the shortest tracking distance of 250 cm. This implementation is expected to be applicable in various fields requiring automated security systems.